Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2009
DOI: 10.1145/1518701.1519025
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of coordination techniques for protecting objects and territories in tabletop groupware

Abstract: Indirect input techniques allow users to quickly access all parts of tabletop workspaces without the need for physical access; however, indirect techniques restrict the available social cues that are seen on direct touch tables. This reduced awareness results in impoverished coordination; for example, the number of conflicts might increase since users are more likely to interact with objects that another person is planning to use. Conflicts may also arise because indirect techniques reduce territorial behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 20 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…As in previous work [6] on coordination techniques on tabletop groupware we showed that a controlled experiment in the form of a game can show effects of coordination techniques. The usage of a game supports the immediate involvement of the participants in the experiment in opposite to a more abstract task.…”
Section: Discussionsupporting
confidence: 75%
“…As in previous work [6] on coordination techniques on tabletop groupware we showed that a controlled experiment in the form of a game can show effects of coordination techniques. The usage of a game supports the immediate involvement of the participants in the experiment in opposite to a more abstract task.…”
Section: Discussionsupporting
confidence: 75%
“…Cao, Wilson, Balakrishnan, Hinckley, & Hudson, 2008;Hilliges, Baur, & Butz, 2007;Jiang, Wigdor, Forlines, & Shen, 2008;Mazalek, Reynolds, & Davenport, 2007;Pinelle, Stach, & Gutwin, 2008;Rick & Rogers, 2008) and comparisons between several design solutions (see e.g. Block, Gutwin, Haller, Gellersen, & Billinghurst, 2008;Jun, Pinelle, Gutwin, & Subramanian, 2008;Marsfhall, Hornecker, Morris, Dalton, & Rogers, 2008;Pinelle, Barjawi, Nacenta, & Mandryk, 2009;Ringel Morris, Cassanego et al, 2006;Ringel Morris, Paepcke, Winograd, & Stamberger, 2006). Tabletop paradigm evaluation: In this last category we include studies comparing the realization of the same activity on a tabletop system and on a given control condition (e.g.…”
Section: Tabletop Devices and Their Evaluationmentioning
confidence: 99%
“…Nevertheless, the 'social protocols' are in general useless due to the overhead of imposing the rules and cause dissatisfaction among the users [5]. Many studies have employed the strategies of conflict avoidance in applications of multi-touch tabletops and large tiled-displays [3] [4] [6] [7].…”
Section: Introductionmentioning
confidence: 99%